Ethnic Stereotypes in the Perception of Advertising by Young People - Nina G. Salmina; Elena V. Zvonova; Nikol A. Pestereva; Pham Hong Nhung (Lomonosov Moscow State University, 2023)
Background. Stereotyping is an important part of social cognition. Therefore, it attracts a lot of attention from psychologists and sociologists. Ethnic stereotypes are not only a reflection of established prejudices and false ideas, but also a kind of social "barometer" indicating possible social problems. Modern studies have revealed the relationship between stereotypes and real ethnic diversity, and also indicate that the subjective feeling of disadvantage is a breeding ground for the emergence and existence of ethnic stereotypes. Objective. The article aims to substantiate theoretically, to identify empirically, as well as to classify ethnic stereotypes in the perception of advertising by young people, representatives of four ethnic groups. Sample. The study involved 88 people, representatives of 4 countries. Methods. The study simulated a situation of interethnic interaction, in which the participants acted as the "authors" of 6 advertising messages and 3 commercials. They had to write stories selecting the "main characters", whose participation would illustrate the attractiveness of the advertised product or service. A set of typical images of representatives of different ethnic groups was proposed. Psychological diagnostics was aimed at establishing differences between groups. were An express questionnaire "Tolerance Index" (G.U. Soldatova, O.A. Kravtsova, O.E. Khukhlaev, L.A. Shaigerova) and emotional empathy questionnaire (Emotional Empathic Tendency Scale, EETS) designed to determine the level of empathic tendencies, the ability to empathize as a personal trait by A. Mehrabian and N. Epstein were used. Results. Areas of social practices where autostereotypes and heterostereotypes appear were identified. Themes where new stereotypes appear were identified. The diagnostics showed that there is no statistically significant difference in the indicators of tolerance and empathy between representatives of the 4 groups. Conclusions. The results of the study can be explained by the fact that participants demonstrated the unity of social group, the youth. The results obtained can be interpreted as evidence that for modern young people, the decisive factor in the formation of stereotypes is information transmitted through various means, which clearly acquires a transnational character.